THE INFLUENCE OF TIKTOK SHOP’S PREDATORY PRICING ON CONSUMER ATTRACTION AND PURCHASING DECISIONS OF FASHION PRODUCTS AMONG GENERATION Z - Ramadhani Dwi Priyanto; Alshaf Pebrianggara; Mochamad Rizal Yulianto (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to empirically examine the effect of predatory pricing strategies on consumer attraction and purchasing decisions of fashion products on TikTok Shop among Generation Z, with consumer attraction serving as a mediating variable. Method: This study employed a quantitative approach with an explanatory research design and analyzed the data using Partial Least Squares Structural Equation Modeling (PLS-SEM). The sample consisted of 100 Generation Z respondents in Indonesia who actively shop for fashion products on TikTok Shop. Data were collected through a five-point Likert scale questionnaire distributed online and analyzed using SmartPLS. Result: The findings indicate that predatory pricing has a significant positive effect on both consumer attraction and purchasing decisions. Consumer attraction was also found to positively influence purchasing decisions and partially mediates the relationship between predatory pricing and purchasing decisions. The R² values for consumer attraction (0.871) and purchasing decisions (0.847) demonstrate very strong explanatory power, while the Q² values for each construct (>0.35) indicate high predictive relevance. Novelty: This study confirms that although extreme pricing strategies can trigger impulsive purchases and increase purchase urgency among Generation Z, long-term reliance on such practices may erode consumer trust and undermine market sustainability. Unlike previous studies that focused primarily on regulatory aspects and SMEs, this research provides empirical evidence of the paradoxical effects of predatory pricing on digital-native consumer behavior.